2000
DOI: 10.1007/s001980070075
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality Following Clinical Fractures

Abstract: To examine the risk of mortality following all clinical fractures, we followed 6459 women age 55-81 years participating in the Fracture Intervention Trial for an average of 3.8 years. All fractures and deaths were confirmed by medical record or death certificate. Clinical fractures were fractures that came to medical attention. Fracture status was used as a time-dependent covariate in proportional hazards models. The 907 women who experienced a fracture were older, had lower bone mineral density and were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
428
4
30

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 824 publications
(475 citation statements)
references
References 15 publications
13
428
4
30
Order By: Relevance
“…Other studies reported that increased mortality after hip and vertebral fractures was consistent over the initial five-year period. (4,6,8,11) In the present study, prevalent morphometric vertebral deformity and prevalence of hip fracture were not associated with increased mortality. Inconsistency between our report and many previous studies can be explained by differences between incidence and prevalence of fracture, because prevalent vertebral deformity and hip fracture in our study included those cases that had developed many years in the past.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 38%
See 1 more Smart Citation
“…Other studies reported that increased mortality after hip and vertebral fractures was consistent over the initial five-year period. (4,6,8,11) In the present study, prevalent morphometric vertebral deformity and prevalence of hip fracture were not associated with increased mortality. Inconsistency between our report and many previous studies can be explained by differences between incidence and prevalence of fracture, because prevalent vertebral deformity and hip fracture in our study included those cases that had developed many years in the past.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 38%
“…M any studies have shown increased fracture risk (1)(2)(3) and mortality (4)(5)(6)(7)(8) after clinical vertebral fracture. Even subjects with no clinical fracture and little pain but with vertebral deformity detected by X-ray showed slightly increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have shown that in postmenopausal women the consequences of vertebral fractures are markedly influenced by the number and severity of prior vertebral fractures [7,27]. It has been reported that patients with multiple fractures are at increased risk of morbidity and mortality [2,14]. Therefore, the recognition of vertebral fractures is critical for the prediction of possible future fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal injuries are common in the elderly, and fractures are associated with a high rate of morbidity and mortality [5,24]. In most healthy adults immobility associated with fracture healing does not significantly impact quality of life of the patient, but in elderly patients the period of convalescence required for fracture repair is a significant cause of post-trauma morbidity and mortality [12,20].…”
Section: Introductionmentioning
confidence: 99%